The Added-on of Ziziphus Jujube Syrup in the Treatment of Chronic Spontaneous Urticaria Resistant to Standard-Dose of Secondary-generation H1 Antihistamine: A Double-Blind Randomized Clinical Trial - Hamid Zare; Seyed Hesamedin Nabavizdeh; Amir Mohamad Jaladat; Mohamad Mehdi Zarshenas; Mozhgan Moghtaderi; Atefeh Basirat; Nahid Nasri (Iranian Journal of Medical Sciences, 2023)
Background: Although antihistamines are the first-line treatment for chronic spontaneous urticaria (CSU), 50% of patients don’t respond to standard doses. In this study, the effectiveness of Ziziphus jujube fruit syrup in combination with antihistamines was assessed in patients with CSU.Methods: This double-blind randomized clinical trial was conducted in Shiraz between December 2019 and December 2020. 64 patients with CSU who had experienced hives for at least six weeks and did not respond to the usual treatments were enrolled in the study. They were randomly assigned to intervention and control groups using permuted block random allocation. For four weeks, the intervention group received 7.5 mL Ziziphus jujube syrup twice a day, while the control group received 7.5 mL simple jujube syrup twice a day. Both groups received cetirizine 10 mg every night. Urticaria activity score (UAS) and CU-Q2oL questionnaires were used to assess urticaria state and sleep quality before and after each week for four consecutive weeks. Data were analyzed using SPSS software version 18, and P<0.05 was considered statistically significant. Results: Before the intervention, there was no statistically significant difference between the two groups’ mean of UAS (P=0.490) and sleep quality (P=0.423). During the follow-up, UAS in the intervention group was significantly lower (P=0.001). Moreover, this difference was significant on the day 28 (P=0.046). During the follow-up, the quality of sleep in both groups improved significantly, and this improvement was more significant in the intervention group.Conclusion: Ziziphus jujube syrup could be an effective adjuvant treatment for CSU.Trial Registration Number: IRCT20190304042916N1.